(untitled) (Orfeu, 2019)
Ernesto Nazareth holds an exemplary position in the debates surrounding the classical-popular dichotomy that are crucial for understanding Brazilian culture throughout the 20th century. Having lived, according to Elizabeth Travassos, “at the threshold between both worlds”, his work, which is now part of the canonic repertoire of both classical and popular musicians, exemplifies clearly the possibility of superposing values and procedures associated with each of these spheres. This paper analyses two recordings of his piece Fon-fon! (one by Eudóxia de Barros, dated 1963, and the other by André Mehmari, in 2014), with the aim of identifying the interpretive resources through which each artist emphasizes the central values pertaining to his or her field – fidelity to the score and to the composer’s intentions, in the case of the classically-trained pianista; and freedom of personal expression in the case of the pianeiro associated with popular music. Our conclusion, however, is that, by following a certain set of values, each interpreter ends up reinforcing and expressing also values pertaining to the other field.